Prospective Patient Reported Outcomes (PRO) Study Assessing Outcomes of Surgically Managed Ankle Fractures. (February 2020) - Gilley, Jasen; Bell, Raheem; Lima, Mateus; Butler, Bennet; Barrett, Joshua E.; Patel, Milap; Kadakia, Anish R.
Background: Ankle fractures are a common cause of morbidity that have increased in incidence over the past decade. The purpose of this study was to compare the outcomes and prognosis of various fracture subtypes by using 2 validated patient-reported outcome measures: the Patient-Reported Outcome Measurement Information System (PROMIS) Physical Function (PF) and Pain Interference (PI) Computer Adaptive Tests (CATs). Methods: Twelve-month postoperative PF and PI CATs were collected for 126 ankle fracture patients presenting between 2014 and 2017. Patients were stratified by ankle fracture subtype and refined by the presence/absence of concomitant deltoid injury or posterior malleolar fracture. Patients defined as members of vulnerable populations and patients presenting more than 2 weeks from time of injury or with prior acute ipsilateral fracture were excluded. The distribution of PF and PI T scores were assessed via a Shapiro-Wilk test and a 1-way analysis of variance. If significant differences were found between groups, pairwise comparisons were tested via Dwass, Steel, and Critchlow-Fligner multiple comparison analysis. Results: Mean values for the PROMIS PF and PI for each fracture subtype were calculated and compared to reference population mean (SD) T scores of 50 (10): isolated lateral malleolar (PF: 50/PI: 51), isolated medial malleolar (PF: 52/PI: 49), bimalleolar (PF: 48/PI: 50), trimalleoar (PF: 47/PI: 51), isolated posterior malleolar (PF: 53/PI: 44), and isolated syndesmotic injury (PF: 60/PI: 46). Shapiro-Wilk test indicated a nonnormal distribution for the postoperative PROMIS PF T scores across all fracture patients ( P = .0421). Conclusion: Operative fixation of an ankle fracture was able to return most patients to the population mean with regard to PROMIS function and pain regardless of fracture type. Level of Evidence: Level II, prospective comparative study.